The Correlation between Knowledge and Compliance with Tooth Brushing to Free Plaque Score of Mentally Disabled Students - Sukarsih, Sukarsih; Silfia, Aida; Asio, Asio; Mardiah, Ainun (Riset Informasi Kesehatan, 2023)
Background: The Jambi Province Riskesdas in 2018 showed that the number of residents who brushed their teeth every day was 96.4%, and only 1.0% did as recommended after breakfast and before going to bed at night. Data shows that 96.5% of students aged 10-14 years brush their teeth every day and only 2.1% brush their teeth in the morning after breakfast and before going to bed.Method: This type of research is descriptive correlational which aims to find whether there is a relationship. The sample in the study were 30 mothers and students at SLBN 1 Jambi City with mental retardation. The sampling technique used purposive sampling method. The data analysis used in this study is the Spearman test. Results: 1) The correlation coefficient and P-value of the relationship between parental knowledge and the level of knowledge of mentally retarded children are 0.492 and 0.006, 2) The correlation coefficient and P-value of the relationship between parental knowledge and adherence to brushing teeth in mentally retarded children are 0.921 and 0.000, 3) The correlation coefficient and P-value of the relationship between the level of knowledge of parents and the free plaque score of mentally retarded children are 0.489 and 0.006, 4) The correlation coefficient and P-value of the relationship between the level of knowledge and adherence to brushing teeth of mentally retarded children are 0.386 and 0.035, 5) The coefficient value the correlation and P-value of the relationship between the level of knowledge and the free plaque score of mentally retarded children were 0.185 and 0.329, 6) The correlation coefficient and P-value of the relationship between children's tooth brushing adherence and the free plaque score of mentally retarded children at SLBN 1 Jambi City were 0.428 and 0.018Conclusion: 1) there is a significant relationship with moderate strength between the knowledge level of parents and the level of knowledge of mentally retarded children, 2) there is a significant relationship with very strong strength between the level of parental knowledge and adherence to brushing teeth in mentally retarded children, 3) there is a significant relationship with has sufficient strength between the level of parental knowledge and the free plaque score of mentally retarded children, 4) there is a significant and low strength relationship between the level of knowledge and adherence to brushing teeth of mentally retarded children, 5) there is no relationship with very low strength between the level of knowledge and the child's free plaque score mentally retarded, 6) there is a significant relationship with sufficient strength between children's tooth brushing compliance with free plaque scores of mentally retarded children at SLBN 1 Jambi City